Evaluation of Three Commercial Interferon-γ Assays in a Bovine Tuberculosis Free Population - Ghielmetti, Giovanni; Landolt, Patricia; Friedel, Ute; Morach, Marina; Hartnack, Sonja; Stephan, Roger; Schmitt, Sarah (Frontiers in Veterinary Science, 2021)
The interferon-gamma (IFN-γ) assay has been used worldwide as an ancillary test for the diagnosis of bovine tuberculosis (bTB). The aim of this study was to describe, based on the bTB-free status in Switzerland, the difference of applying a more stringent cut-off point of 0.05 compared to 0.1 for bTB surveillance. Moreover, the effect of time between blood collection and stimulation, culture results, OD-values, and the influence of testing different breeds were evaluated. Blood samples from a total of 118 healthy cows older than 6 months were tested with three commercial IFN-γ assays. To confirm the bTB-free status of the tested animals and to investigate potential cross-reactions with nontuberculous mycobacteria, pulmonary and abdominal lymph nodes in addition to ileal mucosa from each cattle were used for the detection of viable Mycobacteria spp. by specific culture. Significant differences regarding the proportion of false-positive results between the two Bovigam tests and between Bovigam 2G and ID Screen were found. Samples analysed with Bovigam 2G were 2.5 (95% CI 1.6 - 3.9) times more likely to yield a false-positive test result than samples analysed with Bovigam TB. Similarly, the odds ratio (OR) for testing samples false positive with ID Screen compared to Bovigam TB was 1.9 (95% CI 1.21 to 2.9). The OR for testing false positive with ID Screen compared to Bovigam 2G was less to equally likely with an OR of 0.75 (95% CI 0.5 to 1.1). When using a cut-off of 0.05 instead of 0.1, the OR for a false-positive test result was 2.2 (95% CI 1.6 to 3.1). Samples tested after 6 h compared to a delayed stimulation time of 22-24 h, were more likely to yield a false-positive test result with an OR of 3.9 (95% CI 2.7 to 5.6). In conclusion, the application of a more stringent cut-off of 0.05 with the Bovigam 2G kit generate a questionable high number of false-positive results of one out of three tested animals. Furthermore, specific breeds might show an increased risk to result false-positive in the Bovigam 2G and the ID Screen assays.